PENANAMAN SIKAP SPIRITUAL DAN SIKAP SOSIAL SISWA MELALUI PEMBELAJARAN TEMATIK PADA MADRASAH IBTIDAIYAH - Wati Oviana; Misbahul Jannah; Nisa Juliantika; Najla Desna Fhasya (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
During the learning process there are students who disturb their friends, lack confidence, are not disciplined, are late to school, and cheat. This study aims to describe (1) How to inculcate students' spiritual attitudes and social attitudes in learning planning for class V teachers in MIN 5 Banda Aceh City (2) How to inculcate students' spiritual attitudes and social attitudes in implementing class V teacher learning in MIN 5 Banda Aceh City (3) What are only the obstacles faced by teachers in instilling spiritual attitudes and social attitudes of students in thematic learning of class V teachers at MIN 5 Banda Aceh City. This research uses descriptive quantitative. The subjects in this study were the principal and three fifth grade teachers at MIN 5 Banda Aceh City. Data collection techniques were carried out by analyzing documentation, learning observations and interviews. The results showed that: (1) The cultivation of spiritual attitudes in planning includes praying with a percentage of 33.3%. (2) The cultivation of social attitudes includes honesty, discipline, responsibility, courtesy, confidence with a percentage of 83.3%. (3) The cultivation of spiritual attitudes in the implementation of learning includes all indicators with a percentage of 100% each. (4) The inculcation of social attitudes in the implementation of learning includes all indicators with a percentage of 100% each. (5) The obstacles faced by teachers are the lack of cooperation between the school, parents and the surrounding environment in instilling these attitudes.